Impact of agricultural sector investment development on national economic output - Sastra, Eka; Damanhuri, Didin S.; Achsani, Noer Azam; Yustika, Ahmad Erani (Technium Social Sciences Journal, 2021)
This study aims to capture the investment performance of the agricultural sector in capital formation and the incremental capital output ratio (ICOR) and its relative contribution to the national economy in the 2011-2020 period. ICOR research method is the ratio of changes in output due to changes in capital as an indicator to measure investment performance. The research data used is secondary data obtained from the Central Statistics Agency (BPS). The results of the study show that the investment performance of the food crop agricultural sector has fluctuated throughout 2011-2020. The impact of the policy on the agricultural sector was generally positive, but in that vulnerable year, investment leakage was found that led to efficiency. The cause of the leakage is the behaviour of rent-seeking which is reflected in the time leading up to the elections, namely in 2014 and 2018 with the leakage rate of the investment budget in that year being very high, namely 74.09% and 84.50%, respectively. The year 2012 was marked by an ICOR value close to 0 (zero) accompanied by the growth and performance of the agri-food sector of 12.80%. In 2013 and 2015 the performance of the food crop sector contributed to the economic growth of the food crop sector by 8.65% and 15.78%. Unfortunately, the potential for loss of income in that year was very high, namely Rp. 8.16 trillion and Rp. 17.45 trillion, respectively. The best period for the performance of the food crop agricultural sector occurred in the rent-seeking behaviour that occurred in 2 motives, namely political and economic motives. Political motives occur through the mechanism of the backing system and lobbying. The economic motive is caused by the emergence of transaction costs for the distribution of subsidized fertilizers so that it leads to an increase in the HET for subsidized fertilizers.